Drivers of the sharing economy that affect consumers' usage behavior: Moderation of perceived risk - Óscar Anaya; Iván Manuel De la Vega Hernández (Administrative Sciences, 2022)
In the access to peer-to-peer sharing of goods and services through a technology platform, which is known as the sharing economy, there is no consensus on the factors that motivate consumers. This study aimed to investigate the moderating effect of perceived risk on consumers' participation in the sharing economy in a developing country. Following a quantitative approach, a survey was conducted among 400 consumers in the Metropolitan Zone of Puebla City, Mexico. Partial least squares structural equation modeling (PLS-SEM) was used to analyze the data. Economic benefits, enjoyment, and trust drove the usage behavior of consumers in the sharing economy. In addition, perceived risk significantly moderated the relationships that usage behavior has with the economic benefits and the feeling of the community. As predicted by social exchange theory, the consumers made choices based on a subjective cost-benefit analysis, showing flexibility in the type and amount of rewards. This study contributes to knowledge about customer behavior in the context of the sharing economy.
Keywords: 350; consumer behavior; moderating effect; perceived risk; sharing economy